ANALISIS PENANGANAN KAWASAN PERMUKIMAN KUMUH DI RT 11 RW 01 KELURAHAN DUREN SAWIT, KECAMATAN DUREN SAWIT, KOTA JAKARTA TIMUR - Fauziyah Bagawat Sari; Nadia A.S. Renhoran (Fakultas Teknik Universitas Krisnadwipayana, 2024)
Slum settlements are one of the major urban problems requiring an integrated approach This study aims to analyze the conditions and management strategies for slum areas in Duren Sawit. This study aims to analyze the conditions and management strategies for slum areas in Duren Sawit. The methods used include GIS, regulation-based scoring, and SWOT analysis. The results indicate that the area falls into the “Mild Slum” category, with the main issues being access to clean water and infrastructure. Recommendations focus on improving basic services and community empowerment.